Optimalisasi Pemasaran Ubi Kayu Melalui Pembentukan Kelompok Hasil Panen di Lampung Tengah - Badri Khoirudin; Erlin Kurniati (SUAN PUBLISHER, 2024)
Cassava remains one of the key agricultural commodities in Central Lampung, yet its marketing system continues to encounter significant structural issues. This study explores the optimization of cassava marketing through the formation of harvest groups among local farmers. A qualitative research approach was adopted, involving in-depth interviews and field observations in various farming communities. The research investigates the role of harvest groups in overcoming challenges such as dependence on middlemen, poor infrastructure, limited access to market networks, and fluctuating selling prices.The findings highlight that the establishment of harvest groups improves coordination among farmers and enhances collective bargaining power, thereby enabling better negotiation of prices and access to broader markets. Through collective marketing strategies, farmers gain greater autonomy and reduce reliance on exploitative intermediaries. Additionally, collaboration with cassava processing industries opens opportunities for value-added production and longer-term partnerships.However, the formation and sustainability of these groups are hindered by limited access to working capital, lack of marketing knowledge, and weak logistical frameworks. Therefore, the success of this strategy necessitates multi-stakeholder support, including policy backing from local governments, facilitation of infrastructure development, and financial assistance from institutions. This study underlines the strategic importance of empowering farmers through group-based marketing initiatives to enhance their economic resilience and market competitiveness